Participation and democracy at work. Essays in honour of Harvie Ramsay - Harley, Bill; Hyman, Jeff; Thompson, Paul (New York, 2005)
"Employee participation is a dynamic and contested area of organisational behaviour, attracting continuing academic, practitioner and policy interest and debate. This book will bring together a fresh, critical and comparative perspective on the full range of participation practices, drawing on the work of leading scholars in the field. It is inteded to honour the work of Harvie Ramsay, who died tragically in 2001 and who was a pioneering writer on participation and democracy in this field."